The Performance of the Bandung City Transportation Department in Overcoming Wild Parking Through Crane Information Systems - M. Riza Hamsyari; Nia Karniawati (International Journal of Politic, Public Policy and Environmental Issues, 2023)
Technology that is currently advancing at a rapid rate is unavoidable in daily life because technological progress will continue to coincide with scientific progress. To construct a government system, society's needs must be met in full. Society is essential to the development of a nation. The purpose of this study is to determine how the performance of an agency is overcoming problems that frequently arise in society, such as prohibited parking. The innovation of SIMDEK is the solution to all superfluous parking activities. This research employs a descriptive method, a qualitative method, and a qualitative approach, and its analysis of the results is based on a review of the relevant literature. Consequently, the authors of this study examine performance indicators, including input, process, output, results, benefits, and impact. The transportation agency's top priority in eradicating all violations is this issue. Based on the findings of this study, the efficacy of the transportation service in addressing illegal parking using the crane system has been extremely efficient since 2021. Nonetheless, in terms of supporting facilities for the illegal parking program through the SIMDEK application, this policy eliminates illegal parking by towing vehicles with a hydraulic vehicle. Since there is only one vehicle on the tow truck, the performance of the transport department is severely constrained. Therefore, it can be concluded that the performance of the transportation service through the crane information system (SIMDEK) has a significant effect on illegal parking violations and makes online reporting simpler for citizens.